Value of ultrasound elastography versus transrectal prostatic biopsy in prostatic cancer detection - Amr Abd El Fattah Hassan Gadalla (The Egyptian Journal of Radiology and Nuclear Medicine, 2015)
Objective: To detect the impact of ultrasound elastography in diagnosis of prostatic cancer, and to evaluate its capability in differentiating benign from malignant lesions. Materials and methods: Fifty patients with different prostatic lesions suspicious for malignancy were included. All patients had a conventional B-mode ultrasound examination and color Doppler imaging, and then real time ultrasound elastography was performed in the same session. Finally, the results were compared to the histo-pathological results of those lesions. Results: The addition of Strain ratio parameter for evaluating the elastography images showed the highest sensitivity of 74.2%, specificity of 73.7% and accuracy of 74.0% at a best cutoff point of 5.5 between benign and malignant lesions. Conclusion: Based on our results, prostate US combined with elastography can be a helpful tool for finding malignant lesions. Also it can help in targeting the biopsy site.